Effectiveness of an Inclusive Education-Based Instructional Unit in Enhancing Students’ Knowledge of 3D Clothing Design Software - Hazazi, Bdoor Abdullah; Ejeimi, Sahar Hassan (Journal of Curriculum and Teaching Methodology, 2025)
The current study aimed to design and evaluate the effectiveness of an instructional unit based on an inclusive education strategy for teaching 3D clothing design software to enhance the cognitive achievement of both students with hearing disabilities and hearing students. The study adopted a quasi-experimental design with a one-group pretest-posttest approach. The research sample consisted of 23 students from the Faculty of Human Sciences and Design, Department of Fashion and Textiles at King Abdulaziz University. The sample included 11 students from the Fashion Industry Program for students with severe hearing disabilities and 12 students from the bachelor's Program in Fashion Industry. A cognitive achievement test (pretest/post-test) was administered to measure the knowledge embedded in the instructional unit. The findings revealed a statistically significant difference between the mean ranks of students' scores (overall) in the pretest and posttest cognitive achievement tests, favoring posttest performance. Additionally, results indicated statistically significant differences between the mean ranks of students with hearing disabilities and hearing students in the posttest cognitive achievement test, favoring hearing students. This suggests the effectiveness of the inclusive education-based instructional unit in enhancing students’ cognitive achievement in 3D clothing design software. The study recommends implementing educational strategies for teaching modern technologies in the fashion industry. Moreover, it advocates for the gradual application of inclusive education strategies in other academic courses within the fashion and textiles discipline.
Keywords: Education Unit; Inclusive Education; Technology; 3D Design Software; Cognitive Achievement